Pengaruh Profesionalisme Guru Terhadap Hasil Belajar Siswa Kelas IV di MI Syaikh Zainuddin NW Anjani - Muhammad Ramdani Nur (Al-mujahidah, 2020)
The professionalism of a teacher is one important factor and is one of the main factors that affect the improvement of student learning outcomes. This is what makes the author very interested in conducting research and knowing the extent to which the increase in student learning outcomes is influenced by teacher professionalism. This study aims to determine: Is there an effect of teacher professionalism on the learning outcomes of fourth grade students at MI Syaikh Zainuddin NW Anjani. The type of research used is ex-post facto correlation research. The population of this study was 18 students of class IV MI Syaikh Zainuddin NW Anjani. Samples were taken based on the nonprobability technique. Data collection techniques using a questionnaire (questionnaire) and documentation. The data analysis used was the product moment correlation. From the results of data analysis using statistical analysis of product moment correlation and getting the calculated r (correlation) value is greater than the r value (correlation) table where the r count is 0.974 after being consulted with the r table value at the 5% significant level, the r table value is 0.468. . Thus, it is evident that there is an influence of teacher professionalism on the learning outcomes of grade IV students at MI Syaikh Zainuddin NW Anjani in the 2018/2019 academic year. The author hopes that this thesis can be used as a library and reference for teachers in particular and further researchers in general